Fight against cholera outbreak, efforts and challenges in Malawi - Mictum Miggo; Gracian Harawa; Allan Kangwerema; Knovicks Simfukwe; Chalo Mfune; Jackson Safari; John Thumbiko Kaunda; Joel Kalua; Glory Sefu; Elias Phiri; Parth Patel (2023)
Abstract Cholera is endemic in many African countries with recurrent seasonal outbreaks in parts of the region. Malawi has been experiencing seasonal outbreaks of Cholera since 1998, and it is one of the major public health problems. The current cholera outbreak is one of Malawi's worst cholera outbreaks in the past 10 years. Since the beginning of the outbreak about 56,090 cumulative cases of cholera have been reported with 1712 deaths representing a case fatality rate of 3.1%. This is happening when the country is recovering from the COVID‐19 epidemic, the devastating effects of tropical storms, and is also tackling the polio outbreak. Clearly, the Malawian health system is overstretched. Nevertheless, the country has taken a positive step in responding to the current cholera outbreak. Setting up treatment facilities, stepping up Water, Sanitation, and Hygiene (WASH) initiatives in impacted areas, and improving the surveillance system for early case detection and treatment are some of the actions taken. As the fight against cholera continues there is a need to significantly increase monitoring in all districts, particularly at the community level for early detection and control of the cholera. Considering there are some cross‐border cases from neighboring countries such as Mozambique, good collaboration between the two countries in strengthening surveillance and hygiene practices in the borders will help in controlling the spread of the disease. While it is commendable that dozens of oral cholera vaccines have been given, it should be noted that this provides short‐term prevention. In addressing the nation's ongoing and recurrent cholera outbreaks, we advise prioritizing WASH efforts in addition to oral cholera vaccine administration.